Das Verletzungsspektrum und die Überlastungsschäden beim Fußballsport auf Kunstrasen - Gaulrapp, H.; Siebert, C.; Rosemeyer, B. (Sportverletzung Sportschaden, 1999)
This controlled non-selected cross-sectional study supplies a basic survey on the topic analysing 1783 injuries in 433 of 736 athletes out of a closed collective. Aged 11 to 40 years and having played an average of 3.7 years an artificial turf the players had sustained 38% skin injuries (58% in the legs), 28% sprains (64% in the ankle joints, 21% in the knee joints) and 17% muscle injuries. 76% of all injuries were minor, i.e. leading to an interruption of under one week, only 8% were severe with a break of over 3 weeks. The average risk of injury was 6 per 1000 hours of participation, similar to that in football on natural grass. More than half of the players protocol pain in the joints, muscles or column persisting even one day after the game, which only led to medical assistance in 3% of all cases. Playing football on artificial grass displays a specific pattern of injuries and exertion syndromes without a higher rate or grade of injuries and therefore shows no medical need for restriction.